Implementation of school based management in improfing the quality of teachers - Almy Soleh Wahyu; Happy Fitria; Yessi Fitriani (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The purpose of this study was to describe the implementation of school based management in proving the quality of teachers In State Senior High School No.4 OKU. This research uses qualitative methods with a descriptive approach. The informants as sources in this study were the principal. Deputy principal, teachers, administrative staff and guardian of students. In collecting the data the researcher used were observation, interview and documentation techniques. Based on the research result it can be concluded that First, the principal in State Senior High School No.4 OKU is capable of implementing school based management well. Second, there is an increase in teacher quality as seen from teacher completence. Third, school principals is able to improve teacher quality through planned and gradual programs. Fourth, the principal is able to improve the quality of the school.